Case Management: Towards Developing Principles to Interrupt the Effects of Cumulative Disadvantage in Later Life - Birchall, Elizabeth M. (My University, 2026)
The growing, diverse population of older adults in Canada will require a range of services to address their varied needs. Some older adults are aging with limited personal and practical resources, resulting in later years marked by poor health, difficulty accessing resources and bodies that are old before their time. Many of these older adults are accessing health and social care resources and receiving case management services. This study explores the ability of case management to interrupt the effect of cumulative disadvantage and improve aging. Principles have been developed to support the design, delivery, and evaluation of existing case management programs to provide redress for the effects of cumulative disadvantage and to improve the aging experience. This study is qualitative, informed by a critical theory and interpretivist perspective. A theoretical framework of cumulative inequality (CI) theory and paradigmatic life course approach informed the development of the research design, which employed narrative inquiry. The research was conducted in community agencies in Toronto, Ontario. The study’s findings show that case management can mitigate the effects of accumulated disadvantage and improve the aging experience. The principles developed are that case management must 1) address practical needs, 2) include emotional support, 3) continuity between workers is important, 4) people’s connections to their families and their social supports, as defined by them, are very important and should be given priority in casework, and 5) be realistic and compassionate about what is possible. Further research building on these principles could develop an evidenced based, critically informed model of case management for older adults aging with limited resources resulting from recent or limited accumulation and from structural accumulation of disadvantage.
Case Management and Aging Well
Keywords: Case Managment; Aging; Cumulative Disadvantage; Life Course; Cumulative Inequality Theory